Diretrizes curriculares nacionais da odontologia e análise dos projetos pedagógicos dos cursos do estado de São Paulo - Ferraz, Daiana (2015)
The National Curricular Guidelines (DCN) of the 2002 Dentistry Undergraduate course are guidelines to be observed in curricular organization that must be necessarily adopted by all higher education institutions (HEI). The overall objective of this study was to analyze the pedagogical projects of the courses (PPC) Dental Public Universities of the State of São Paulo (SP) in the light of DCN. This research is qualitative. The study subjects were five dental courses of SP who had their PPC reformulated after the DCN. The first collection of information was through secondary data obtained from the PPS of each educational institution. The documentary analysis of PPC courses was held in the light of DCN for graduation in dentistry and PPC courses were analyzed using an array of analytical categories. The eight analytical categories used in the analysis of PPC were divided into two areas: 1. Professional profile (general profile, health care, health management and health education) and 2 Course structure (organization of the course, design of teaching learning, teaching methods and learning and assessment). The second source of information consisted of primary data collected through semi-structured interview with the five coordinators of the courses, defined as the study subjects. The semi- structured interviews were conducted in person with three coordinators and through Skype with two coordinators of the courses, and were composed of questions about PPC and student education from the perspective of DCN and acting for the NHS. Qualitative analysis of the interviews took place from the content analysis technique, thematic modality defined by Bardin. The analysis of PPC in the light of DCN demonstrated suitability in general, with some observations regarding verbatim parts of the DCN in PPC, not matching the reality of course, little detail in relation to health management at all PPC analyzed and teaching methodologies learning and assessment still on traditional modes of education in relation to the powers described in DCN.